From Gasotransmitter to Immunomodulator: The Emerging Role of Hydrogen Sulfide in Macrophage Biology - Alex Cornwell; Alireza Badiei (MDPI AG, 2023)
Hydrogen sulfide (H2S) has been increasingly recognized as a crucial inflammatory mediator in immune cells, particularly macrophages, due to its direct and indirect effects on cellular signaling, redox homeostasis, and energy metabolism. The intricate regulation of endogenous H2S production and metabolism involves the coordination of transsulfuration pathway (TSP) enzymes and sulfide oxidizing enzymes, with TSP's role at the intersection of the methionine pathway and glutathione synthesis reactions. Additionally, H2S oxidation mediated by sulfide quinone oxidoreductase (SQR) in mammalian cells may partially control cellular concentrations of this gasotransmitter to induce signaling. H2S is hypothesized to signal through the posttranslational modification known as persulfidation, with recent research highlighting the significance of reactive polysulfides, a derivative of sulfide metabolism. Overall, sulfides have been identified as having promising therapeutic potential to alleviate proinflammatory macrophage phenotypes, which are linked to the exacerbation of disease outcomes in various inflammatory conditions. H2S is now acknowledged to have a significant influence on cellular energy metabolism by affecting the redox environment, gene expression, and transcription factor activity, resulting in changes to both mitochondrial and cytosolic energy metabolism processes. This review covers recent discoveries pertaining to the involvement of H2S in macrophage cellular energy metabolism and redox regulation, and the potential implications for the inflammatory response of these cells in the broader framework of inflammatory diseases.